2012
DOI: 10.1371/journal.pone.0052077
|View full text |Cite
|
Sign up to set email alerts
|

Natural Parasite Infection Affects the Tolerance but Not the Response to a Simulated Secondary Parasite Infection

Abstract: Parasites deplete the resources of their host and can consequently affect the investment in competing traits (e.g. reproduction and immune defence). The immunocompetence handicap hypothesis posits that testosterone (T) mediates trade-offs between parasite defence and reproductive investment by suppressing immune function in male vertebrates while more recently a role for glucocorticoids (e.g. cortisol (C)) in resource allocation has been suggested. These hypotheses however, have not always found support in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
(71 reference statements)
3
15
0
Order By: Relevance
“…Infestation with one parasite can put substantial constraints on the ability of a host to respond to secondary infestations which are likely in the wild due to the ubiquity of more than one parasite species present in natural environments [36]. Similar effects of multiple parasite infestation have also been observed in a closely related mole-rat species, the highveld mole-rat ( Cryptomys hottentotus pretoriae ) [37]. Hence, energy savings obtained in larger groups may have played an important role in overcoming constraints to the evolution of sociality in bathyergids.…”
Section: Discussionmentioning
confidence: 85%
“…Infestation with one parasite can put substantial constraints on the ability of a host to respond to secondary infestations which are likely in the wild due to the ubiquity of more than one parasite species present in natural environments [36]. Similar effects of multiple parasite infestation have also been observed in a closely related mole-rat species, the highveld mole-rat ( Cryptomys hottentotus pretoriae ) [37]. Hence, energy savings obtained in larger groups may have played an important role in overcoming constraints to the evolution of sociality in bathyergids.…”
Section: Discussionmentioning
confidence: 85%
“…Although initially proposed by Folstad and Karter (1992) as a negative feedback to the ICHH, this hypothesis has received far less attention and offers an alternative and important mechanism on how the trade-off between reproduction and immunity is modulated. Lutermann et al (2012) found that highveld mole-rats (Cryptomys hottentotus pretoriae) that were naturally infected by cestodes had lower testosterone levels than those who were not infected. They also found that, when faced with an immune challenge through the subcutaneous injection of a lipopolysaccharide (LPS) to stimulate the innate immune system, there was a significant decrease in testosterone levels as well as an increase in cortisol levels.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the impact of parasite infection on vertebrate‐host GCs, quantitative methods are required to assess whether parasite‐induced changes in these hormones show general responses in their direction and magnitude across host–parasite associations. It is especially important to establish the broad nature of GC responses in the context of infectious disease dynamics, such as whether they may be expected in host–parasite associations not yet studied, because chronic elevation of GCs could depress immunity and make infected hosts more prone to secondary infections (Lutermann, Bodenstein, & Bennett, ).…”
Section: Introductionmentioning
confidence: 99%
“…To address such inconsistencies, it is essential to establish whether these discrepancies in GC responses stem from methodological or biological phenomena-questions suitable for meta-anal-infected hosts more prone to secondary infections (Lutermann, Bodenstein, & Bennett, 2012).…”
mentioning
confidence: 99%